Effect of Improved Housing Design and Sexing on Carcass Traits and Fatty Acid Composition of Meat in Broiler Chicken - Simsek, U. G.; Ciftci, M.; Cerci, I. H.; Gurses, M.; Guvenc, M. (Garuda Scientific Publications, 2009)
To study the effects of improved housing design (sand bedding and provision of perches) and sexing on carcass traits and fatty acid composition, 480 Ross-308 chicks were assigned to two groups including equal number of male and female. At d 42, 8 representative males and 8 females were slaughtered from each group. Their carcasses were evaluated. Fatty acid composition of whole carcass (4 males, 4 females) and meat from breast and left thigh from the remaining 4 males and 4 females were evaluated. Carcass traits did not differ between groups. Total PUFA, omega-3 and omega-6 ratios increased and total SFA and MUFA ratios decreased (P<0.001), in the improved housing group. Total SFA was found to be higher in female than male broiler (P<0.05). It was concluded that improved housing with perches and sand bedding improved chicken meat quality and increased total polyunsaturated fatty acid ratio of the meat. Sexing significantly affected fatty acids composition of meat.
Keywords: Broiler chicken; housing design; sexing; carcass traits; meat fatty acid composition